Kinerja Parkir pada Gedung Parkir Sepeda Motor di Institut Teknologi Nasional Bandung - Alfare Jakaria, Dicky; Triana, Sofyan; Fitrianingsih, Ligar (FSTPT Indonesia, 2024)
The Bandung National Institute of Technology is a private tertiary institution in Bandung, where more and more students bring motorcycles yearly despite the limited parking space available. The method in this study uses the 1998 Parking Facility Planning and Operation Guidelines. Conducted field checks; the SRP was reduced from the original planning of 1258 SRP to 1174 SRP due to the H Beam iron construction blocking it. Due to the inconvenience factor and the incompatibility of the guidelines on the parking pattern and road width, a re-planning was carried out, and 1113 new SRPs were produced. The analysis of parking vehicle capacity obtained the highest number of parking accumulations of 749 vehicles. In contrast, for the available parking spaces, namely 1174, the parking building can still accommodate parked cars. An increase in parking space in 2033 resulted in 978 vehicles, and there is still 196 SRP remaining space. However, in 2040, it will no longer be able to accommodate parking needs, which will cause a shortage of 4 SRP. ABSTRAK Institut Teknologi Nasional Bandung merupakan perguruan tinggi swasta di Kota Bandung yang dimana semakin banyaknya mahasiswa dari tahun ke tahun yang membawa sepada motor disamping keterbatasan lahan parkir yang ada. Metode pada penelitian ini menggunakan Pedoman Perencanaan dan Pengoperasian Fasilitas Parkir Tahun 1998. Dilakukan pengecekan di lapangan, SRP berkurang dari semula perencanaan 1258 SRP menjadi 1174 SRP dikarenakan adanya konstruksi besi H Beam yang menghalangi. Dikarenakan adanya faktor ketiaknyamanan dan ketidaksesuaian pedoman pada pola parkir dan lebar jalan maka dilakukan perencanaan kembali dan dihasilkan SRP baru sebanyak 1113 SRP. Hasil analisis kapasitas kendaraan parkir diperoleh jumlah akumulasi parkir tertinggi 749 kendaraan sedangkan untuk ruang parkir yang tersedia yaitu 1174, maka gedung parkir tersebut masih mampu menampung kendaraan yang parkir. Peningkatan ruang parkir pada tahun 2033 didapatkan hasil 978 kendaraan, masih terdapat sisa ruang sebanyak 196 SRP. Namun, pada 2040 sudah tidak dapat menampung kebutuhan parkir yang dimana mengalami kekurangan 4 SRP.